MITIGATION OF CALCIUM CARBONATE INORGANIC SCALING - HARON, MOHAMED FAKHRULLAH (Universiti Teknologi Petronas, 2011)
Inorganic scale is a very common problem in the oil and gas industry. Common types of scale include calcium carbonate, magnesium carbonate, calcium sulphate, barium sulphate, strontium sulphate and radium sulphate. Carbonate deposits depend on changing operational conditions such as pressure and temperature whereas sulphate scale deposits depend on mixing incompatible waters and seawater rich in sulphate. The focus of this project will be on calcium carbonate scale which is one of the most common types of scale. Unresolved calcium carbonate scale problem may lead to loss in production and damage to equipments which will eventually lead to severe economic loss. In order to tackle the scale problem, scale inhibitors are introduced into wells. Example of conventional scale inhibitors which is widely used is diethylenetriaminepentakis (methylenephosphonica acid) or DTPMP. The problems with conventional scale inhibitors are most of them are harmful towards the environment. This project will look into green alternatives for calcium carbonate scale inhibitors. The green alternatives consist of gambir extracts, aloe vera gels and green tea extracts. Laboratory tests will be performed to evaluate their potential in inhibiting the formation of calcium carbonate deposits. Comparisons in terms of their effectiveness in delaying the deposition of calcium carbonate will be made between the three materials for calcium carbonate scale inhibitors.